Diversity and composition of plants in ex-mining revegetation lands for cement raw materials in South Kalimantan, Indonesia - MOCHAMAD ARIEF SOENDJOTO; I WAYAN KEDEP SUDIARTA; M. INDRA Z. CANGARA; WISNU ADI PATRIA; MAULANA KHALID RIEFANI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Soendjoto MA, Sudiarta IWK, Cangara MIZ, Patria WA, Riefani MK. 2025. Diversity and composition of plants in ex-mining revegetation lands for cement raw materials in South Kalimantan, Indonesia. Biodiversitas 26: 670-680. PT Indocement Tunggal Prakarsa Tbk carries out open-pit mining to obtain cement raw materials in Kotabaru District, South Kalimantan, Indonesia, for the Tarjun-12 Factory. The company then undertakes the challenging task of revegetating ex-mining lands. However, there are no existing records of plant species post-revegetation, which occurred 13 to 16 years ago. This research is unique in its approach, aiming to document plant species and analyze their presence after revegetation. The methodology involves placing an observation path on each ex-mining land, with each path comprising 10 observation plots (20 m x 20 m) for recording woody plants at tree level. Each observation plot includes a small plot (10 m x 10 m) for data collection at the pole level, one plot (5 m x 5 m) for sapling level and non-woody plants (herbs), and one plot (2 m x 2 m) for seedling level and non-woody plants (grasses, ferns). The data were then analyzed after obtaining the importance value index, diversity index (Shannon-Wiener), and similarity index (Sorensen). The study revealed that more than 90% of the 155 plant species (54 families) are spontaneously grown plants, and most plant communities between ex-mining lands are dissimilar. The highest diversity is in woody plants at the sapling level and also trees on ex-laterite mining land. These results represent unique baseline data for 13-16 years post-revegetation.